2017
DOI: 10.1088/1361-6668/aa87f1
|View full text |Cite
|
Sign up to set email alerts
|

A novel concept of high temperature superconducting undulator

Abstract: The available variety of commercial high temperature superconducting (HTS) coated conductors resulted in the development of many different HTS based applications. One promising application to realize superconducting undulators for table top free electron lasers considers meander-structured stacked HTS tapes to provide the desired sinusoidal magnetic field pattern. One of the biggest challenges of this layout is to keep the resistance of the joints between the stacked tapes small. This paper presents a novel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…While PMUs are standard in storage rings to date and often serve as a reference, SCUs regained strong interest in the last two decades, also due to the development and improvement in high-temperature superconducting (HTS) wires and tapes and the possibility of avoiding liquid He temperatures [4]. Indeed, such high-temperature SCUs have been developed since 2014 in Los Alamos [5], Argonne [6], Seoul [7], Beijing [8], and Karlsruhe [9,10]. The achievable field B 0 naturally depends on operating temperature besides gap and periodicity, where the performance at 4 K is comparable to Nb-Ti SCUs while much more cost-effective higher temperatures, even 77 K, are possible on the cost of lower B 0 values.…”
Section: Lt01)mentioning
confidence: 99%
“…While PMUs are standard in storage rings to date and often serve as a reference, SCUs regained strong interest in the last two decades, also due to the development and improvement in high-temperature superconducting (HTS) wires and tapes and the possibility of avoiding liquid He temperatures [4]. Indeed, such high-temperature SCUs have been developed since 2014 in Los Alamos [5], Argonne [6], Seoul [7], Beijing [8], and Karlsruhe [9,10]. The achievable field B 0 naturally depends on operating temperature besides gap and periodicity, where the performance at 4 K is comparable to Nb-Ti SCUs while much more cost-effective higher temperatures, even 77 K, are possible on the cost of lower B 0 values.…”
Section: Lt01)mentioning
confidence: 99%
“…CC BY 3.0. sinusoidal field at 2 mm above the center of a single meandertype YBCO tape structured with picosecond laser pulses [92]. In 2017, Holubek et al proposed a novel winding scheme named JUST for making a jointless meander-type ReBCO planar SCU, as shown in figure 10(b); the numerical simulation indicated that an on-axis field B 0 of 0.5 T could be obtained at 4 mm magnetic gap in a meander-type SCU8 consisting of thirty 12 mm wide, copper-free ReBCO tape stacks in each coil module [90].…”
Section: Meander-type Rebco Planarmentioning
confidence: 99%
“…have not yet delivered performance superior to NbTi or Nb 3 Sn undulators [8][9][10][11]. A promising approach for achieving high B 0 for a short period λ u is to employ a staggered-array bulk HTS undulator (BHTSU) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%